Analisis Pengendalian Piutang Terhadap Piutang Bank Emok di Desa Tempuran - Gunawan, Syahrul; Sandi, Santi Pertiwi Hari; Patoni, Khaerudin Sidik (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study uses a qualitative method using a triangulation approach that can be used to ensure data validity by verifying information from various sources. Bank Emok is one of the non-bank financial institutions in Indonesia that is now increasingly popular, especially among rural or village communities. Urgent needs encourage people to seek quick loan solutions to meet their needs. Bank Emok offers a money lending program and quick solutions to financial problems. With the existence of these non-formal institutions, it is considered that the community can make it easier to get money. However, every loan certainly has risks, one of the risks that occurs is bad debt. This study aims to determine the lending procedure at Bank Emok, and to analyze the control of receivables at Bank Emok in Tempuran Village. Data were collected through observation, interviews and documentation and then reanalyzed. The results of this study indicate that Bank Emok activities in Tempuran Village implement clear lending procedures and the existence of a joint liability system on customer loans minimizes the occurrence of bad debt.